Economic Analysis of Marketed and Marketable Surplus of Wheat Production in Gwalior District of Madhya Pradesh - Shailendra Sharma, Rahul Singh, D.U.M. Rao, R. Roy Burman and Mukesh Singh (Indian Journal of Extension Education, 2018)
The study on marketed and marketable surplus of wheat was conducted in Gwalior district of Madhya Pradesh.The study revealed that maximum (nearly 68 percent) farmers (in all categories of small, medium and large)preferred Channel IV, i.e., regulated markets for marketing wheat. Even among small farmers the preferencefor regulated market channel is a positive indicator for farmers’ prosperity. However, some farmers preferredto sell their marketed surplus through channels I and II, i.e., through village merchants. The study furtherrevealed that the total marketable surplus was estimated 77.74 per cent. In case of small farms, the percentageof marketable surplus was 46.74 per cent. The marketable surplus increased as the increased size of farmsincreases. It was estimated at 62.56 percent in medium farms and 85.62 percent in large farms.